Genomics of response to porcine reproductive and respiratory syndrome virus in purebred and crossbred sows: antibody response and performance following natural infection vs. vaccination. (29th March 2021) - Sanglard, Leticia P; Hickmann, Felipe M W; Huang, Yijian; Gray, Kent A; Linhares, Daniel C L; Dekkers, Jack C M; Niederwerder, Megan C; Fernando, Rohan L; Braccini Neto, Joseph; Serão, Nick V L
Abstract: Antibody response, measured as sample-to-positive (S/P) ratio, to porcine reproductive and respiratory syndrome virus (PRRSV ) following a PRRSV-outbreak ( S/P Outbreak ) in a purebred nucleus and following a PRRSV-vaccination ( S/P Vx ) in commercial crossbred herds have been proposed as genetic indicator traits for improved reproductive performance in PRRSV-infected purebred and PRRSV-vaccinated crossbred sows, respectively. In this study, we investigated the genetic relationships of S/P Outbreak and S/P Vx with performance at the commercial (vaccinated crossbred sows) and nucleus level (non-infected and PRRSV-infected purebred sows), respectively, and tested the effect of previously identified SNP for these indicator traits. Antibody response was measured on 541 Landrace sows 54 d after the start of a PRRSV outbreak, and on 906 F1 (Landrace × Large White) gilts 50 d after vaccination with a commercial PRRSV vaccine. Reproductive performance was recorded for 711 and 428 Landrace sows before and during the PRRSV outbreak, respectively, and for 811 vaccinated F1 animals. The estimate of the genetic correlation ( r g ) of S/P Outbreak with S/P Vx was 0.72 ± 0.18. The estimates of r g of S/P Outbreak with reproductive performance in vaccinated crossbred sows were low to moderate, ranging from 0.05 ± 0.23 to 0.30 ± 0.20. The estimate of r g of S/P Vx with reproductive performance in non-infected purebred sows was moderate and favorable with number born alive (0.50 ± 0.23) but low (0 ± 0.23 to −0.11 ± 0.23) with piglet mortality traits. The estimates of r g of S/P Vx were moderate and negative (−0.38 ± 0.21) with number of mummies in PRRSV-infected purebred sows and low with other traits (−0.30 ± 0.18 to 0.05 ± 0.18). Several significant associations ( P 0 > 0.90) of previously reported SNP for S/P ratio (ASGA0032063 and H3GA0020505) were identified for S/P ratio and performance in non-infected purebred and PRRSV-exposed purebred and crossbred sows. Genomic regions harboring the major histocompatibility complex class II region significantly contributed to the genetic correlation of antibody response to PRRSV with most of the traits analyzed. These results indicate that selection for antibody response in purebred sows following a PRRSV outbreak in the nucleus and for antibody response to PRRSV vaccination measured in commercial crossbred sows are expected to increase litter size in purebred and commercial sows.